# What is the derivative of this? y = t^(2) √(t-2)

Then teach the underlying concepts
Don't copy without citing sources
preview
?

#### Explanation

Explain in detail...

#### Explanation:

I want someone to double check my answer

1
Mar 8, 2018

$\frac{\mathrm{dy}}{\mathrm{dx}} = 2 t \sqrt{t - 2} + {t}^{2} / \left(2 \sqrt{t - 2}\right)$

#### Explanation:

By product rule, let $f \left(x\right) = {t}^{2}$, let $g \left(x\right) = \sqrt{t - 2}$

$\frac{d}{\mathrm{dx}} f \left(x\right) \cdot g \left(x\right)$ = $f ' \left(x\right) \cdot g \left(x\right) + f \left(x\right) \cdot g ' \left(x\right)$

$f ' \left(x\right) = 2 t$, $g ' \left(x\right) = \frac{1}{2 \sqrt{t - 2}}$

Hence, $\frac{\mathrm{dy}}{\mathrm{dx}} = 2 t \sqrt{t - 2} + {t}^{2} / \left(2 \sqrt{t - 2}\right)$

• 19 minutes ago
• 19 minutes ago
• 23 minutes ago
• 27 minutes ago
• 3 minutes ago
• 7 minutes ago
• 9 minutes ago
• 10 minutes ago
• 11 minutes ago
• 12 minutes ago
• 19 minutes ago
• 19 minutes ago
• 23 minutes ago
• 27 minutes ago